Using Smartphones When Eating Increases Caloric Intake in Young People: An Overview of the Literature - La Marra, Marco; Caviglia, Giorgio; Perrella, Raffaella (Frontiers in Psychology, 2020)
Recent literature highlights that the use of smartphones during meals increases the number of calories ingested in young people. Although the distraction interferes with physiological signals of hunger and satiety, a social facilitation effect has also been suggested. Cognition is a pivotal component in regulating food intake, and activities requiring high perceptual demands should be discouraged during meals.